The local nature of housing markets: new evidence - Pin-Te Lin (Regional Studies, Regional Science)
This research examines whether much of the variation in house price changes is mainly driven by local or national factors. Employing a novel data containing both capital appreciation and income component in the US metropolitan statistical areas, results show that macroeconomic factors, absorbed by time fixed effects, account for 59% of the variation in capital gains and 4% of the variation in rental yields. Overall, this empirical study is an important complement to the prior literature assuming that the nature of housing markets is primarily local, particularly evidenced in the cross-sectional income returns. The results provide implications for balanced national development and portfolio diversification strategy.